The History of Film Adaptation in Malaysia: The Long Journey of Its Rise and Fall: (Sejarah Filem Adaptasi di Malaysia: Sebuah Perjalanan Jatuh Bangun yang Panjang) (Malay Literature, 2018)
Morris Beja in his book Film and Literature: An Introduction, said that since the Academy Awards was introduced in 1927-28, about three quarters of the award for best film was won by film adaptations. This is proof that film adaptation is a form of art that has gained the attention of the world community and was a well-known form of narrative in the 19th and 20th centuries in Europe. This paper takes the initiative to trace the history of film adaptations in general by focusing on such films in Malaysia. Findings of the study reveal that the history of film adaptation in Malaysia started in 1933 during the filming enterprise of Cathay Film and Malay Film in Singapore up to the setting up of Merdeka Studio in Kuala Lumpur in the 1970s and beyond. The film industry in Malaysia faced many problems including the influx of imported films from Indonesia and the commercialization factor that did not guarantee profits. However, around 2006, concerted efforts were reinforced to adapt literary works into films, through workshops and competitions organized by Malaysian government bodies such as Dewan Bahasa dan Pustaka (DBP), National Film Development Corporation (FINAS) and Radio and Television Malaysia (RTM).Keywords: film adaptation, history, Cathay Keris, Malay Film, Merdeka Studio